2005
DOI: 10.1111/j.1472-765x.2005.01688.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of seven Vibrio virulence genes among Vibrio alginolyticus and Vibrio parahaemolyticus strains from the coastal mariculture systems in Guangdong, China

Abstract: Investigation of seven Vibrio virulence genes amongAims: To investigate the distribution of the virulence of two Vibrio species among different strains obtained from the mariculture systems on the coast of Guangdong in China and the correlation between the virulence strains and the virulence genes among Vibrio alginolyticus. Methods: Besides three strains, 72 V. alginolyticus strains and seven Vibrio parahaemolyticus strains were examined by PCR or semi-nested PCR for the virulence genes (tlh, trh, tdh, toxR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
3
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 29 publications
7
106
3
3
Order By: Relevance
“…The plasmids were transformed into E. coli JM109 competent cells, and the sequence of the cloned genes in the vector pMD 18-T was confirmed by DNA sequencing (Invitrogen Biotech, Shanghai, China). Previous studies have shown the distribution of different virulence genes among V. cholerae, V. mimicus, V. alginolyticus and V. parahaemolyticus (Ghosh et al, 1997;Sechi et al, 2000;Shi et al, 1998;Shinoda and Nakagawa, 2004;Xie et al, 2005). Our results indicate that the virulence genes such as toxS, flaB and flaC are widely distributed among different vibrios, whereas zot and tcpA only exit in a few vibrios.…”
mentioning
confidence: 49%
“…The plasmids were transformed into E. coli JM109 competent cells, and the sequence of the cloned genes in the vector pMD 18-T was confirmed by DNA sequencing (Invitrogen Biotech, Shanghai, China). Previous studies have shown the distribution of different virulence genes among V. cholerae, V. mimicus, V. alginolyticus and V. parahaemolyticus (Ghosh et al, 1997;Sechi et al, 2000;Shi et al, 1998;Shinoda and Nakagawa, 2004;Xie et al, 2005). Our results indicate that the virulence genes such as toxS, flaB and flaC are widely distributed among different vibrios, whereas zot and tcpA only exit in a few vibrios.…”
mentioning
confidence: 49%
“…It inhabits broadly coastal seawater environments and causes many clinical infections and tremendous damage in fish, shellfish and crustaceans culture. In South China, V. alginolyticus is found to be the dominant pathogen in seawater and have caused huge loss in marine aquaculture industry (Huang and He 2002;Hu et al 2005;Xie et al 2005). The conventional culture-based method for detection of V. alginolyticus is time-consuming and labour-intensive, thus gradually replaced by PCR-based methods (Chen et al 2002;Di Pinto et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Vibrio alginolyticus is an important opportunistic bacterial pathogen for both human and aquatic animals (Reina Prieto and Heravs Palazon 1993;Caruso et al 1998;HervioHeath et al 2002;George et al 2005;Xie et al 2005;Gonzalez-Escalona et al 2006). Several clinical infections caused by V. alginolyticus were reported (Levine and Griffin 1993;Reina Prieto and Heravs Palazon 1993;GahrnHansen and Hornstrup 1994;Gomez et al 2003), as well as tremendous damage caused in fish, shellfish and crustaceans (Anderson et al 1988;Lightner 1988;Lee et al 1996;Vandenberghe et al 1999;Hörmansdorfer et al 2000;Huang and He 2002;George et al 2005;Gó mezLeó n et al 2005;Hu et al 2005;Jayaprakash et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that Vibrio species represents an important recipient of some V. cholerae and V. parahaemolyticus virulence genes transfers (Xie et al, 2005). Snoussi et al (2008), reported the diffusion of six V. cholerae virulence genes among 28 V. alginolyticus strains isolated from the Mediterranean seawater.…”
Section: Discussionmentioning
confidence: 99%